An Isoflavone from Dipteryx alata Vogel is Active against the in Vitro Neuromuscular Paralysis of Bothrops jararacussu Snake Venom and Bothropstoxin I, and Prevents Venom-Induced Myonecrosis - Ferraz, Miriele C.; Yoshida, Edson H.; Tavares, Renata V. S.; Cogo, Jose C.; Cintra, Adelia C. O.; Dal Belo, Chariston A.; Franco, Luiz M.; Santos, Marcio G. dos; Resende, Flavia A. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Hyslop, Stephen; Puebla, Pilar; et al. (Mdpi Ag, 2014)
Snakebite is a neglected disease and serious health problem in Brazil, with most bites being caused by snakes of the genus Bothrops. Although serum therapy is the primary treatment for systemic envenomation, it is generally ineffective in neutralizing the local effects of these venoms. In this work, we examined the ability of 7,8,3'-trihydroxy-4'-methoxyisoflavone (TM), an isoflavone from Dipteryx alata, to neutralize the neurotoxicity (in mouse phrenic nerve-diaphragm preparations) and myotoxicity (assessed by light microscopy) of Bothrops jararacussu snake venom in vitro. The toxicity of TM was assessed using the Salmonella microsome assay (Ames test). Incubation with TM alone (200 mu g/mL) did not alter the muscle twitch tension whereas incubation with venom (40 mu g/mL) caused irreversible paralysis. Preincubation of TM (200 mu g/mL) with venom attenuated the venom-induced neuromuscular blockade by 84% +/- 5% (mean +/- SEM; n = 4). The neuromuscular blockade caused by bothropstoxin-I (BthTX-I), the major myotoxic PLA(2) of this venom, was also attenuated by TM. Histological analysis of diaphragm muscle incubated with TM showed that most fibers were preserved (only 9.2% +/- 1.7% were damaged; n = 4) compared to venom alone (50.3% +/- 5.4% of fibers damaged; n = 3), and preincubation of TM with venom significantly attenuated the venom-induced damage (only 17% +/- 3.4% of fibers damaged; n = 3; p < 0.05 compared to venom alone). TM showed no mutagenicity in the Ames test using Salmonella strains TA98 and TA97a with (+S9) and without (-S9) metabolic activation. These findings indicate that TM is a potentially useful compound for antagonizing the neuromuscular effects (neurotoxicity and myotoxicity) of B. jararacussu venom.
Keywords: ames test; bothropstoxin-I; 7,8,3'-trihydroxy-4'-methoxyisoflavone; neuromuscular junction; Salmonella mutagenicity; snake venoms